Unveiling the flames: macrophage pyroptosis and its crucial role in liver diseases - Ni, Linghong; Chen, Dandan; Zhao, Yanping; Ye, Rongxia; Fang, Peng (Frontiers in Immunology, 2024)
Macrophages play a critical role in innate immunity, with approximately 90% of the total macrophage population in the human body residing in the liver. This population encompasses both resident and infiltrating macrophages. Recent studies highlight the pivotal role of liver macrophages in various aspects such as liver inflammation, regeneration, and immune regulation. A novel pro-inflammatory programmed cell death, pyroptosis, initially identified in macrophages, has garnered substantial attention since its discovery. Studies investigating pyroptosis and inflammation progression have particularly centered around macrophages. In liver diseases, pyroptosis plays an important role in driving the inflammatory response, facilitating the fibrotic process, and promoting tumor progression. Notably, the role of macrophage pyroptosis cannot be understated. This review primarily focuses on the role of macrophage pyroptosis in liver diseases. Additionally, it underscores the therapeutic potential inherent in targeting macrophage pyroptosis.